THE CHARACTERISTICS OF LAMPUNG LOCAL SAND AS CASTING SAND IN THE METAL CASTING PROCESS - Yusup Hendronursito; David Candra Birawidha; Kusno Isnugroho; Fathan Bahfie; Wulanda Yurista Persatika; Sapriyadi Sapriyadi (Balai Riset dan Standardisasi Industri Palembang, 2019)
In Indonesia, the demand for sand was mainly fulfilled using sand brought from Java although with a very expensive transportation cost. For the Sumatran region, the province of Lampung is rich in quartz sand that has the potential to act as substitute to the Java originated sand. This experiment aims to characterize sand from Tanjung Bintang and Maringgai of Lampung province as the prerequisite for the recondition process for its use as casting sand. In this experiment, two kinds of sand sample extracted from Lampung province were characterized. Casting sand from Ceper of Middle Java province was analyzed as comparison. The results showed that although the water and clay content of Ceper sand was higher than that of Lampung sand, the Lampung sand itself had finer particle size and morphology which was shown by higher Grain Finenesss Number (GFN) than Ceper casting sand at 48.49 for Tanjung Bintang sand and 47.61 for Maringgai sand as opposed to Ceper’s 31.31. Elemental analysis showed that Lampung sand contained more Al2O3 and MgO than its Java counterpart. These elements contribute to the improvement of the ability of produced casting sand to resist higher temperature and reducing the need for binder material.